Cooperation and conflict between state and local government - Hanson, Russell L. 1953-; Zeemering, Eric S. (Rowman & Littlefield, 2021)
"This collection of essays on state-local relations provides undergraduate students in political science and public administration with an overview of both cooperation and conflict in state-local relations. Contributors to the volume analyze the politicization of state-local relations while also detailing how both policy and administrative coordination continue. By engaging leading experts from around the country, the book draws in policy examples from different states, speaking to a broad U.S. audience. Undergraduate students are the primary audience for this book, but the content also serves as a helpful reference for state and local government officials who recognize that state-local relations is a shifting and changing landscape that requires more deliberate and thoughtful attention"--
Keywords: Beziehung; Kommune; Staat; Föderalismus; USA; State-local relations / United States; State-local relations; United States; Aufsatzsammlung